Delineation of a Human Mendelian Disorder of the DNA Demethylation Machinery: TET3 Deficiency. - Beck, David B; Petracovici, Ana; He, Chongsheng; Moore, Hannah W; Louie, Raymond J; Ansar, Muhammad; Douzgou, Sofia; Sithambaram, Sivagamy; Cottrell, Trudie; Santos-Cortez, Regie Lyn P; Prijoles, Eloise J; Bend, Renee; et al. (Am J Hum Genet, 2020)
Germline pathogenic variants in chromatin-modifying enzymes are a common cause of pediatric developmental disorders. These enzymes catalyze reactions that regulate epigenetic inheritance via histone post-translational modifications and DNA methylation. Cytosine methylation (5-methylcytosine [5mC]) of DNA is the quintessential epigenetic mark, yet no human Mendelian disorder of DNA demethylation has yet been delineated. Here, we describe in detail a Mendelian disorder caused by the disruption of DNA demethylation. TET3 is a methylcytosine dioxygenase that initiates DNA demethylation during early zygote formation, embryogenesis, and neuronal differentiation and is intolerant to haploinsufficiency in mice and humans. We identify and characterize 11 cases of human TET3 deficiency in eight families with the common phenotypic features of intellectual disability and/or global developmental delay; hypotonia; autistic traits; movement disorders; growth abnormalities; and facial dysmorphism. Mono-allelic frameshift and nonsense variants in TET3 occur throughout the coding region. Mono-allelic and bi-allelic missense variants localize to conserved residues; all but one such variant occur within the catalytic domain, and most display hypomorphic function in an assay of catalytic activity. TET3 deficiency and other Mendelian disorders of the epigenetic machinery show substantial phenotypic overlap, including features of intellectual disability and abnormal growth, underscoring shared disease mechanisms.
Keywords: Adult; Amino Acid Sequence; Autistic Disorder; Child; Child, Preschool; Developmental Disabilities; Dioxygenases; DNA Demethylation; Embryonic Development; Female; Gene Expression Regulation, Developmental; Growth Disorders; Humans; Infant; Male; Middle Aged; Movement Disorders; Pedigree; Protein Conformation; Sequence Homology; Young Adult

Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance. - Liaqat, Khurram; Schrauwen, Isabelle; Raza, Syed Irfan; Lee, Kwanghyuk; Hussain, Shabir; Chakchouk, Imen; Nasir, Abdul; Acharya, Anushree; Abbe, Izoduwa; Umair, Muhammad; Ansar, Muhammad; Ullah, Irfan; et al. (J Hum Genet, 2019)
Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca1.3 protein expressed in inner hair cells, atria and SAN, induces loss-of-function in channel activity and underlies SANDD. To date, only one variant c.1208_1209insGGG:p.(G403_V404insG) has been reported for SANDD syndrome. We studied five Pakistani families with SANDD and characterized a new missense variant p.(A376V) in CACNA1D in one family, and further characterized the founder variant p.(G403_V404insG) in four additional pedigrees. We show that affected individuals in the four families which segregate p.(G403_V404insG) share a 1.03 MB haplotype on 3p21.1 suggesting they share a common distant ancestor. In conclusion, we identified new and known variants in CACNA1D in five Pakistani families with SANDD. This study is of clinical importance as the CACNA1D founder variant is only observed in families from the Khyber Pakhtunkhwa (KPK) province, in Pakistan. Therefore, screening patients with congenital deafness for SAN dysfunction in this province could ensure adequate follow-up and prevent cardiac failure associated with SAN.
Keywords: Adolescent; Calcium Channels, L-Type; Deafness; Female; Heart Diseases; Humans; Male; Mutation; Pakistan; Pedigree; Prognosis; Sinoatrial Node

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability. - Santos-Cortez, Regie Lyn P; Khan, Valeed; Khan, Falak Sher; Mughal, Zaib-Un-Nisa; Chakchouk, Imen; Lee, Kwanghyuk; Rasheed, Memoona; Hamza, Rifat; Acharya, Anushree; Ullah, Ehsan; Saqib, Muhammad Arif Nadeem; Abbe, Izoduwa; et al. (Hum Genet, 2018)
Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were performed. DNA samples from affected family member(s) from every pedigree underwent exome sequencing. Identified rare damaging exome variants were tested for co-segregation with ID using Sanger sequencing. For seven ARID families, variants were identified in genes not previously associated with ID, including: EI24, FXR1 and TET3 for which knockout mouse models have brain defects; and CACNG7 and TRAPPC10 where cell studies suggest roles in important neural pathways. For two families, the novel ARID genes CARNMT1 and GARNL3 lie within previously reported ID microdeletion regions. We also observed homozygous variants in two ID candidate genes, GRAMD1B and TBRG1, for which each has been previously reported in a single family. An additional 14 families have homozygous variants in established ID genes, of which 11 variants are novel. All ARID genes have increased expression in specific structures of the developing and adult human brain and 91% of the genes are differentially expressed in utero or during early childhood. The identification of novel ARID candidate genes and variants adds to the knowledge base that is required to further understand human brain function and development.
Keywords: Adult; Consanguinity; Family; Female; Genes, Recessive; Genetic Markers; Humans; Intellectual Disability; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Autosomal-Recessive Hearing Impairment Due to Rare Missense Variants within S1PR2. - Santos-Cortez, Regie Lyn P; Faridi, Rabia; Rehman, Atteeq U; Lee, Kwanghyuk; Ansar, Muhammad; Wang, Xin; Morell, Robert J; Isaacson, Rivka; Belyantseva, Inna A; Dai, Hang; Acharya, Anushree; Qaiser, Tanveer A; et al. (Am J Hum Genet, 2016)
The sphingosine-1-phosphate receptors (S1PRs) are a well-studied class of transmembrane G protein-coupled sphingolipid receptors that mediate multiple cellular processes. However, S1PRs have not been previously reported to be involved in the genetic etiology of human traits. S1PR2 lies within the autosomal-recessive nonsyndromic hearing impairment (ARNSHI) locus DFNB68 on 19p13.2. From exome sequence data we identified two pathogenic S1PR2 variants, c.323G>C (p.Arg108Pro) and c.419A>G (p.Tyr140Cys). Each of these variants co-segregates with congenital profound hearing impairment in consanguineous Pakistani families with maximum LOD scores of 6.4 for family DEM4154 and 3.3 for family PKDF1400. Neither S1PR2 missense variant was reported among ∼120,000 chromosomes in the Exome Aggregation Consortium database, in 76 unrelated Pakistani exomes, or in 720 Pakistani control chromosomes. Both DNA variants affect highly conserved residues of S1PR2 and are predicted to be damaging by multiple bioinformatics tools. Molecular modeling predicts that these variants affect binding of sphingosine-1-phosphate (p.Arg108Pro) and G protein docking (p.Tyr140Cys). In the previously reported S1pr2(-/-) mice, stria vascularis abnormalities, organ of Corti degeneration, and profound hearing loss were observed. Additionally, hair cell defects were seen in both knockout mice and morphant zebrafish. Family PKDF1400 presents with ARNSHI, which is consistent with the lack of gross malformations in S1pr2(-/-) mice, whereas family DEM4154 has lower limb malformations in addition to hearing loss. Our findings suggest the possibility of developing therapies against hair cell damage (e.g., from ototoxic drugs) through targeted stimulation of S1PR2.
Keywords: Amino Acid Sequence; Asian Continental Ancestry Group; Chromosomes, Human, Pair 19; Exome; Genes, Recessive; Hearing Loss; Humans; Lod Score; Logistic Models; Lysophospholipids; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype; Receptors, Lysosphingolipid; Sphingosine

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities

Mitral regurgitation as a phenotypic manifestation of nonphotosensitive trichothiodystrophy due to a splice variant in MPLKIP. - Shah, Khadim; Ali, Raja Hussain; Ansar, Muhammad; Lee, Kwanghyuk; Chishti, Muhammad Salman; Abbe, Izoduwa; Li, Biao; Smith, Joshua D; Nickerson, Deborah A; Shendure, Jay; Coucke, Paul J; Steyaert, Wouter; et al. (BMC Med Genet, 2016)
BACKGROUND: Nonphotosensitive trichothiodystrophy (TTDN) is a rare autosomal recessive disorder of neuroectodermal origin. The condition is marked by hair abnormalities, intellectual impairment, nail dystrophies and susceptibility to infections but with no UV sensitivity. METHODS: We identified three consanguineous Pakistani families with varied TTDN features and used homozygosity mapping, linkage analysis, and Sanger and exome sequencing in order to identify pathogenic variants. Haplotype analysis was performed and haplotype age estimated. A splicing assay was used to validate the effect of the MPLKIP splice variant on expression. RESULTS: Affected individuals from all families exhibit several TTDN features along with a heart-specific feature, i.e. mitral regurgitation. Exome sequencing in the probands from families ED168 and ED241 identified a homozygous splice mutation c.339 + 1G > A within MPLKIP. The same splice variant co-segregates with TTDN in a third family ED210. The MPLKIP splice variant was not found in public databases, e.g. the Exome Aggregation Consortium, and in unrelated Pakistani controls. Functional analysis of the splice variant confirmed intron retention, which leads to protein truncation and loss of a phosphorylation site. Haplotype analysis identified a 585.1-kb haplotype which includes the MPLKIP variant, supporting the existence of a founder haplotype that is estimated to be 25,900 years old. CONCLUSION: This study extends the allelic and phenotypic spectra of MPLKIP-related TTDN, to include a splice variant that causes cardiomyopathy as part of the TTDN phenotype.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Alleles; Asian Continental Ancestry Group; Child; Cloning, Molecular; Exome; Female; Genetic Linkage; Haplotypes; HEK293 Cells; Homozygote; Humans; Introns; Male; Mitral Valve Insufficiency; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA Splicing; Sequence Analysis, DNA; Trichothiodystrophy Syndromes; Young Adult

Novel mutations in the genes TGM1 and ALOXE3 underlying autosomal recessive congenital ichthyosis. - Ullah, Rahim; Ansar, Muhammad; Durrani, Zaka Ullah; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Muhammad, Dost; Ali, Mahboob; Zia, Muhammad; Ayub, Muhammad; Khan, Suliman; Smith, Josh D; Nickerson, Deborah A; et al. (Int J Dermatol, 2016)
BACKGROUND: Ichthyoses are clinically characterized by scaling or hyperkeratosis of the skin or both. It can be an isolated condition limited to the skin or appear secondarily with involvement of other cutaneous or systemic abnormalities. METHODS: The present study investigated clinical and molecular characterization of three consanguineous families (A, B, C) segregating two different forms of autosomal recessive congenital ichthyosis (ARCI). Linkage in three consanguineous families (A, B, C) segregating two different forms of ARCI was searched by typing microsatellite and single nucleotide polymorphism marker analysis. Sequencing of the two genes TGM1 and ALOXE3 was performed by the dideoxy chain termination method. RESULTS: Genome-wide linkage analysis established linkage in family A to TGM1 gene on chromosome 14q11 and in families B and C to ALOXE3 gene on chromosome 17p13. Subsequently, sequencing of these genes using samples from affected family members led to the identification of three novel mutations: a missense variant p.Trp455Arg in TGM1 (family A); a nonsense variant p.Arg140* in ALOXE3 (family B); and a complex rearrangement in ALOXE3 (family C). CONCLUSION: The present study further extends the spectrum of mutations in the two genes involved in causing ARCI. Characterizing the clinical spectrum resulting from mutations in the TGM1 and ALOXE3 genes will improve diagnosis and may direct clinical care of the family members.
Keywords: Adolescent; Chromosomes, Human, Pair 14; Chromosomes, Human, Pair 17; Codon, Nonsense; Consanguinity; Female; Gene Rearrangement; Genotype; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis, Lamellar; Lipoxygenase; Male; Mutation, Missense; Pakistan; Pedigree; Phenotype; Transglutaminases; Young Adult

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

A homozygous missense variant in type I keratin KRT25 causes autosomal recessive woolly hair. - Ansar, Muhammad; Raza, Syed Irfan; Lee, Kwanghyuk; Shahi, Shamim; Acharya, Anushree; Dai, Hang; Smith, Joshua D; Shendure, Jay; Bamshad, Michael J; Nickerson, Deborah A; Santos-Cortez, Regie Lyn P; Ahmad, Wasim; et al. (J Med Genet, 2015)
BACKGROUND: Woolly hair (WH) is a hair abnormality that is primarily characterised by tightly curled hair with abnormal growth. METHODS: In two unrelated consanguineous Pakistani families with non-syndromic autosomal recessive (AR) WH, homozygosity mapping and linkage analysis identified a locus within 17q21.1-q22, which contains the type I keratin gene cluster. A DNA sample from an affected individual from each family underwent exome sequencing. RESULTS: A homozygous missense variant c.950T>C (p.(Leu317Pro)) within KRT25 segregated with ARWH in both families, and has a combined maximum two-point LOD score of 7.9 at ϴ=0. The KRT25 variant is predicted to result in disruption of the second α-helical rod domain and the entire protein structure, thus possibly interfering with heterodimerisation of K25 with type II keratins within the inner root sheath (IRS) of the hair follicle and the medulla of the hair shaft. CONCLUSIONS: Our findings implicate a novel gene involved in human hair abnormality, and are consistent with the curled, fragile hair found in mice with Krt25 mutations, and further support the role of IRS-specific type I keratins in hair follicle development and maintenance of hair texture.
Keywords: Child; Child, Preschool; Consanguinity; Hair; Hair Diseases; Humans; Keratins, Type I; Male; Mutation, Missense; Pakistan; Pedigree; Sequence Analysis, DNA

Mutation of ATF6 causes autosomal recessive achromatopsia. - Ansar, Muhammad; Santos-Cortez, Regie Lyn P; Saqib, Muhammad Arif Nadeem; Zulfiqar, Fareeha; Lee, Kwanghyuk; Ashraf, Naeem Mahmood; Ullah, Ehsan; Wang, Xin; Sajid, Sundus; Khan, Falak Sher; Amin-ud-Din, Muhammad; Smith, Joshua D; et al. (Hum Genet, 2015)
Achromatopsia (ACHM) is an early-onset retinal dystrophy characterized by photophobia, nystagmus, color blindness and severely reduced visual acuity. Currently mutations in five genes CNGA3, CNGB3, GNAT2, PDE6C and PDE6H have been implicated in ACHM. We performed homozygosity mapping and linkage analysis in a consanguineous Pakistani ACHM family and mapped the locus to a 15.12-Mb region on chromosome 1q23.1-q24.3 with a maximum LOD score of 3.6. A DNA sample from an affected family member underwent exome sequencing. Within the ATF6 gene, a single-base insertion variant c.355_356dupG (p.Glu119Glyfs*8) was identified, which completely segregates with the ACHM phenotype within the family. The frameshift variant was absent in public variant databases, in 130 exomes from unrelated Pakistani individuals, and in 235 ethnically matched controls. The variant is predicted to result in a truncated protein that lacks the DNA binding and transmembrane domains and therefore affects the function of ATF6 as a transcription factor that initiates the unfolded protein response during endoplasmic reticulum (ER) stress. Immunolabeling with anti-ATF6 antibodies showed localization throughout the mouse neuronal retina, including retinal pigment epithelium, photoreceptor cells, inner nuclear layer, inner and outer plexiform layers, with a more prominent signal in retinal ganglion cells. In contrast to cytoplasmic expression of wild-type protein, in heterologous cells ATF6 protein with the p.Glu119Glyfs*8 variant is mainly confined to the nucleus. Our results imply that response to ER stress as mediated by the ATF6 pathway is essential for color vision in humans.
Keywords: Activating Transcription Factor 6; Adolescent; Animals; Asian Continental Ancestry Group; Color Vision Defects; Consanguinity; DNA Mutational Analysis; Exome; Female; Frameshift Mutation; Genotyping Techniques; Homozygote; Humans; Limit of Detection; Male; Mice; Mice, Inbred C57BL; Pakistan; Pedigree; Phenotype; Retina; Signal Transduction

Adenylate cyclase 1 (ADCY1) mutations cause recessive hearing impairment in humans and defects in hair cell function and hearing in zebrafish. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Giese, Arnaud P; Ansar, Muhammad; Amin-ud-Din, Muhammad; Rehn, Kira; Wang, Xin; Aziz, Abdul; Chiu, Ilene; Hussain Ali, Raja; Smith, Joshua D; Shendure, Jay; et al. (Hum Mol Genet, 2014)
Cyclic AMP (cAMP) production, which is important for mechanotransduction within the inner ear, is catalyzed by adenylate cyclases (AC). However, knowledge of the role of ACs in hearing is limited. Previously, a novel autosomal recessive non-syndromic hearing impairment locus DFNB44 was mapped to chromosome 7p14.1-q11.22 in a consanguineous family from Pakistan. Through whole-exome sequencing of DNA samples from hearing-impaired family members, a nonsense mutation c.3112C>T (p.Arg1038*) within adenylate cyclase 1 (ADCY1) was identified. This stop-gained mutation segregated with hearing impairment within the family and was not identified in ethnically matched controls or within variant databases. This mutation is predicted to cause the loss of 82 amino acids from the carboxyl tail, including highly conserved residues within the catalytic domain, plus a calmodulin-stimulation defect, both of which are expected to decrease enzymatic efficiency. Individuals who are homozygous for this mutation had symmetric, mild-to-moderate mixed hearing impairment. Zebrafish adcy1b morphants had no FM1-43 dye uptake and lacked startle response, indicating hair cell dysfunction and gross hearing impairment. In the mouse, Adcy1 expression was observed throughout inner ear development and maturation. ADCY1 was localized to the cytoplasm of supporting cells and hair cells of the cochlea and vestibule and also to cochlear hair cell nuclei and stereocilia. Ex vivo studies in COS-7 cells suggest that the carboxyl tail of ADCY1 is essential for localization to actin-based microvilli. These results demonstrate that ADCY1 has an evolutionarily conserved role in hearing and that cAMP signaling is important to hair cell function within the inner ear.
Keywords: Adenylyl Cyclases; Animals; Cercopithecus aethiops; Codon, Nonsense; COS Cells; Cyclic AMP; Cytoplasm; Ear, Inner; Female; Hair Cells, Auditory; Hearing Loss; Humans; Labyrinth Supporting Cells; Male; Mice; Zebrafish

Biallelic truncating mutations in FMN2, encoding the actin-regulatory protein Formin 2, cause nonsyndromic autosomal-recessive intellectual disability. - Law, Rosalind; Dixon-Salazar, Tracy; Jerber, Julie; Cai, Na; Abbasi, Ansar A; Zaki, Maha S; Mittal, Kirti; Gabriel, Stacey B; Rafiq, Muhammad Arshad; Khan, Valeed; Nguyen, Maria; Ali, Ghazanfar; et al. (Am J Hum Genet, 2014)
Dendritic spines represent the major site of neuronal activity in the brain; they serve as the receiving point for neurotransmitters and undergo rapid activity-dependent morphological changes that correlate with learning and memory. Using a combination of homozygosity mapping and next-generation sequencing in two consanguineous families affected by nonsyndromic autosomal-recessive intellectual disability, we identified truncating mutations in formin 2 (FMN2), encoding a protein that belongs to the formin family of actin cytoskeleton nucleation factors and is highly expressed in the maturing brain. We found that FMN2 localizes to punctae along dendrites and that germline inactivation of mouse Fmn2 resulted in animals with decreased spine density; such mice were previously demonstrated to have a conditioned fear-learning defect. Furthermore, patient neural cells derived from induced pluripotent stem cells showed correlated decreased synaptic density. Thus, FMN2 mutations link intellectual disability either directly or indirectly to the regulation of actin-mediated synaptic spine density.
Keywords: Adolescent; Adult; Base Sequence; Chromosome Disorders; Cohort Studies; Consanguinity; Egypt; Exome; Female; Genes, Recessive; Genetic Linkage; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Intellectual Disability; Male; Microfilament Proteins; Molecular Sequence Data; Nuclear Proteins; Pakistan; Pedigree; Sequence Analysis, DNA; Sequence Deletion